2005
DOI: 10.1016/j.anihpc.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Positive solutions to superlinear second-order divergence type elliptic equations in cone-like domains

Abstract: We study the problem of the existence and nonexistence of positive solutions to a superlinear second-order divergence type elliptic equation with measurable coefficients −∇ · a · ∇u = u p ( * ), p > 1, in an unbounded cone-like domain G ⊂ R N (N ≥ 3). We prove that the critical exponent p * (a, G) = inf{p > 1 : ( * ) has a positive supersolution at infinity in G } for a nontrivial conelike domain is always in (1, N N −2 ) and in contrast with exterior domains depends both on the geometry of the domain G and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…In particular, in [13] it was shown that the critical exponent p * = N N −2 is stable with respect to the change of the Laplacian by a second-order uniformly elliptic divergence type operator with measurable coefficients, perturbed by a potential, for a sufficiently wide class of potentials (see also [14] for equations of type (1.3) in exterior domains in the presence of first order terms). In [15,16] equation (1.3) and the corresponding equation with the divergence type elliptic operators was studied on cone-like domains, and it was shown that the value of the critical exponent is dependent on the geometry of the domain even in the case of the Laplacian, and on the behaviour of the coefficients of the elliptic operator at infinity. The method developed in these papers shows that the exact value of the critical exponent can be determined based upon the precise asymptotics at infinity of the minimal harmonic function with respect to the operator (Green's function) and the "maximal" harmonic function.…”
Section: ) Has (Infinitely Many) Positive Solutions Outside a Ball Fomentioning
confidence: 99%
“…In particular, in [13] it was shown that the critical exponent p * = N N −2 is stable with respect to the change of the Laplacian by a second-order uniformly elliptic divergence type operator with measurable coefficients, perturbed by a potential, for a sufficiently wide class of potentials (see also [14] for equations of type (1.3) in exterior domains in the presence of first order terms). In [15,16] equation (1.3) and the corresponding equation with the divergence type elliptic operators was studied on cone-like domains, and it was shown that the value of the critical exponent is dependent on the geometry of the domain even in the case of the Laplacian, and on the behaviour of the coefficients of the elliptic operator at infinity. The method developed in these papers shows that the exact value of the critical exponent can be determined based upon the precise asymptotics at infinity of the minimal harmonic function with respect to the operator (Green's function) and the "maximal" harmonic function.…”
Section: ) Has (Infinitely Many) Positive Solutions Outside a Ball Fomentioning
confidence: 99%
“…The problem of the existence and nonexistence of positive solutions to a weak linear second-order divergence type elliptic equation in an unbounded cone-like domains was studied in [7].…”
Section: Introductionmentioning
confidence: 99%
“…A number of mathematicians [2,5,7,13,15,16] took the study of quasilinear elliptic problems in unbounded domains. The problem of the existence and nonexistence of positive solutions to a weak linear second-order divergence type elliptic equation in an unbounded cone-like domains was studied in [7].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of existence and nonexistence of positive solutions to a weak linear second-order divergence type elliptic equation in an unbounded cone-like domain was studied in [6].…”
Section: Introductionmentioning
confidence: 99%
“…After creating the linear theory, a number of mathematicians [4,6,[8][9][10] took the study of semi-linear elliptic problems in unbounded domains. The problem of existence and nonexistence of positive solutions to a weak linear second-order divergence type elliptic equation in an unbounded cone-like domain was studied in [6].…”
Section: Introductionmentioning
confidence: 99%